Mexico : 2013 Review Under the Flexible Credit Line Arrangement. (IMF Staff Country Reports; Country Report ;, 2013)
This paper discusses Mexico' Review Under the Flexible Credit Line (FCL) Arrangement. Significant progress has been made in advancing far-reaching structural reforms, signaling Mexico's commitment to address deep-rooted impediments to growth. The economy slowed down in early 2013, but is expected to recover starting in the second half of the year. Mexico's financial markets have functioned reasonably well through the recent global volatility, although with some currency depreciation and a rise in long-term government bond yields. The IMF Staff recommends completion of the review under the FCL arrangement for Mexico, subject to the Board's assessment in the context of the 2013 Article IV consultation.